Síntese e caracterização de dextrinas esterificadas com ácido málico a partir dos amidos de mandioca e milho - Almeida, Jacqueline de Florio (2016)
Native starches have some technological disadvantages which stimulate researches for modification, aimed improve physicochemical properties and promote specific functional properties. Modifications as dextrinization and esterification are widely used, however, despite recent advances about modified starches, there is still little information about the properties of esterified dextrins. The aim of this study was to prepare and characterize esterified dextrins from cassava and maize starches using malic acid. The modification of starches was performed by heating a dried mixture (≤ 3%) of starch and malic acid (2.5; 5.0; 7.5 % w/w). To evaluate the effect of an acid catalyst, tests were prepared with addition of HCl (0.05% w/w) under the same conditions. The starch pyrodextrinization in presence of malic acid produces esterified dextrins with low degree of substitution (DS) and anionic properties, as well as high clarity of paste, cold solubility and low viscosity at high solids contents. The macromolecular degradation decreases the amylose content values after modification, as well as the intrinsic viscosity values. However, the dextrins with high GS showed higher intrinsic viscosity in DMSO, which suggests the occurrence of crosslinking in the dextrins with a higher concentration of malic acid. The results of dextrose equivalent (DE) were dependent of malic acid concentration and values ranged from 6.69 to 11.33% in dextrins from cassava starch, and 8.56 to 12.38% in dextrins from maize starch. Color variations indicated its direct dependence on pyrodextrinization conditions and showed trends to yellow tones, typical feature of pyrodextrin. In X-ray diffraction, was observed that modification changed x-ray pattern in dextrins from cassava starch and decreases the relative crystallinity (RC) of the granules from cassava and maize starches, and its granular morphology (SEM) and thermal properties were affected, it was not observed phase transition related to the gelatinization in DSC analysis.